Determinants of sexual function and dysfunction in men and women with stroke: A systematic review. Issue 7 (8th June 2017) - Dusenbury, Wendy; Palm Johansen, Pernille; Mosack, Victoria; Steinke, Elaine E.
Summary: Aim: The aim of this systematic review was to examine determinants of sexual function and dysfunction in men and women poststroke, and to evaluate effectiveness of interventions. Methods: A systematic review was conducted using the databases of PubMed, Medline, CINAHL, Cochrane, and Psychinfo, for studies published between January, 2000 and October, 2016. Included were original research, adult ≥18 years, English language, and experimental and non‐experimental designs. Excluded were studies of stroke caused by sexual activity, stroke triggered unusual behaviours, and changes in sexual orientation. Studies were evaluated for quality using The Effective Public Health Practice Project Quality Assessment Tool for Quantitative Studies. Of 19 studies reviewed, 13 were descriptive, three case‐controlled and three intervention/randomised controlled trials (RCTs) designs. Results: Participants across studies were predominantly men (90%), with moderate erectile dysfunction (ED), and mild depression. Changes in sexual activity, sexual dissatisfaction and sexual dysfunction were common, including decreased libido, orgasmic problems and ED, significantly worse from pre to poststroke. Results for side of hemiparesis and sexual dysfunction were inconclusive. Sexual rehabilitation interventions differed, but resulted in improved sexual satisfaction, sexual activity frequency and erectile function in two studies. Conclusions: Sexual dysfunction commonly occurred poststroke, continuing for months or as long as 2 years. Intervention studies were limited, with only two RCTs, thus, firm conclusions cannot be made. Few studies included women or younger stroke patients, indicating the need for further RCTs with larger and more diverse samples.